1973
DOI: 10.1111/j.1532-5415.1973.tb01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Stature and Aging*

Abstract: The study series consisted of 100 women and 100 men over the age of 45 who remembered their heights at the age of 20. Ninety women and 36 men also recalled their weights at age 20. The combined cortical thickness and the cortical index of both clavicles were measured, as well as the height and weight. The reduction of height for the 45–59 age group in women was 1.8 cm, and in men 1.1 cm; for the 60–69 age group in women it was 2.7 cm, and in men 1.7 cm; and for the 70+ age group in women it was 2.8 cm, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Spine extensor muscle strength was found to be lower in severe FP patients. This supports the notion that back extensors play a key role in the pathophysiology of FP 14,15 . In severe FP patients, reduced force of the ankle plantarflexor and dorsiflexor muscles and significantly shorter key functional muscle lengths were found.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Spine extensor muscle strength was found to be lower in severe FP patients. This supports the notion that back extensors play a key role in the pathophysiology of FP 14,15 . In severe FP patients, reduced force of the ankle plantarflexor and dorsiflexor muscles and significantly shorter key functional muscle lengths were found.…”
Section: Discussionsupporting
confidence: 86%
“…The intervertebral disks undergo the most dramatic age‐related changes of all connective tissue, 10,11 which can cause kyphosis 12,13 . Decreased muscle strength can also cause kyphosis 14,15 . Back extensor strength decreases with age and is associated with reduced levels of physical activity 16 and with a decrease in BMD of the spine 17 …”
mentioning
confidence: 99%
“…This study and also others could not detect any such correlation [3,16]. It has been shown earlier that the size of the kyphosis is multi-factorial [9,11,14,16,28,38,50]. The present findings suggested that even severe or multiple fracture deformities in at least a few vertebrae had limited effects on the kyphosis.…”
Section: Influence Of Kyphosis and Lordosissupporting
confidence: 48%
“…Previous studies [1][2][3] suggested that with aging there is a loss of height in males and females, with a greater decline in females, particularly after the age of 40 years [4]. Men lose 3% of bone mass per decade, while women after the menopause may lose up to 8%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the average loss of height from age 20 to ages 65-75 years is 4 cm, and it is 7.5 cm by ages 85-94 years [5]. These data include both cross-sectional [1][2][3] and longitudinal studies [3,6].…”
Section: Introductionmentioning
confidence: 99%